سنن اربعہ کے مؤلفین کے حالات زندگی: تحقیقی جائزہ: The Life Situations of the Authors of the Four Sunans: A Research Review - Dr. Mirza Safdar baig; Farrah Sarwar; Naheema BiBi (International Research Journal of Arabic and Islamic Studies, 2024)
The Sunan Arba'a, comprising four renowned Hadith collections—Sunan Abi Dawood, Sunan an-Nasa'i, Sunan Ibn Majah, and Jami' at-Tirmidhi—are significant in the Islamic tradition for their comprehensive compilation of prophetic traditions. This research paper delves into the lives and contributions of the authors of these collections. Abu Dawood, born in Sistan (present-day Iran), was a prominent 9th-century scholar known for his meticulous compilation methodology. His Sunan Abu Dawood is esteemed for its focus on jurisprudential hadiths. An-Nasa'i, originally from Khurasan, also thrived in the 9th century. His Sunan is celebrated for its rigorous criteria in selecting authentic hadiths, making it a crucial source for Islamic jurisprudence. Ibn Majah, from Qazvin (Iran), offered a more accessible approach, integrating unique narrations in his Sunan, contributing significantly to the diversity of hadith literature. Lastly, at-Tirmidhi from Tirmidh (Uzbekistan) was distinguished for his comprehensive analysis and classification of hadiths, blending jurisprudential, ethical, and theological traditions in his Jami'. This paper critically analyzes their scholarly journeys, methodological innovations, and the socio-political contexts that influenced their works. Through examining their biographical backgrounds, educational pursuits, and the scholarly networks they were part of, this study underscores the pivotal role these scholars played in preserving and transmitting the prophetic traditions. Their contributions are not merely confined to their compilations but extend to their influence on subsequent generations of Islamic scholars and the evolution of hadith sciences.